2005
DOI: 10.1111/j.1471-4159.2004.02968.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear factor‐κB signaling pathway by interleukin‐1 after hypoxia/ischemia in neonatal rat hippocampus and cortex

Abstract: Perinatal hypoxia/ischemia (HI) is a common cause of neurological deficits in children. Interleukin-1 (IL-1) activity has been implicated in HI-induced brain damage. However, the mechanisms underlying its action in HI have not been characterized. We used a 7-day-old rat model to elucidate the role of nuclear factor-jB (NF-jB) activation in HI stimulation of IL-1 signaling. HI was induced by permanent ligation of the left carotid artery followed by 90 min of hypoxia (7.8% O 2 ). Using ELISA assays, we observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 66 publications
4
74
0
Order By: Relevance
“…This finding is consistent with other reports of HI-induced effects (11,14,30,31). In addition, the observed up-regulation of iNOS (NOS2) and an iNOS transcriptionactivating element, NF-B, in the HI animals compared with the shams confirms prior immunohistological data (32).…”
Section: Discussionsupporting
confidence: 83%
“…This finding is consistent with other reports of HI-induced effects (11,14,30,31). In addition, the observed up-regulation of iNOS (NOS2) and an iNOS transcriptionactivating element, NF-B, in the HI animals compared with the shams confirms prior immunohistological data (32).…”
Section: Discussionsupporting
confidence: 83%
“…The transcription factor NF-B assumes a key role in many biological processes including cellular stress responses and regulates apoptosis and inflammation (Ridder et al, 2009). Activation of NF-B is crucial for the inflammatory responses leading to gene expression of pro-inflammatory cytokines and mediators in immunocytes (Hu et al, 2005;Ridder et al, 2009). In this study, we demonstrated that the diabetic rats had an increased basal level of the gene expression of pro-inflammatory cytokines IL-1 and TNF-, and inflammatory mediators COX-2 and iNOS as compared to that of non-diabetic rats.…”
Section: Discussionsupporting
confidence: 50%
“…Since then, other authors have described mitigation of the induction of IL-1β through reduction of NF-κB activation [27]. In 2014, Hu et al [28 ]described that the level of IL-1β in the cerebral cortex was elevated 3-12 h following the induction of hypoxia/ischemia and observed an increase in cell death along with the activity of the transcription factor NF-κB. …”
Section: Discussionmentioning
confidence: 99%